Merkel cell carcinoma: a new radiation-induced cancer? - Bertrand, M; Mirabel, X; Desmedt, E; Vercambre-Darras, S; Martin de Lassalle, E; Bouchindhomme, B; Guerreschi, P; Martinot, V; Mortier, L (Annales de dermatologie et de vénéréologie, 2013)
Merkel cell carcinoma (MCC), a rare and aggressive neuroendocrine tumour, appears primarily on sun-exposed areas in light-skinned elderly subjects. UV exposure and profound immunosuppression (particularly in a setting of solid organ transplantation, haematological malignancies, HIV) constitute the principal risk factors. The aetiopathogenesis of this cancer is not known, although a polyomavirus involved in the oncogenic process was recently discovered. The carcinogenic effect of ionizing radiation, while not clearly established, has been suspected in rare cases involving the onset of MCC in irradiated zones. We report a new case of case of MCC in a patient previously undergoing radiotherapy. A 59-year-old-man underwent radiotherapy for a Darier-Ferrand dermatofibrosarcoma on the left shoulder and developed MCC at the same site 38 years later. The time between radiotherapy and diagnosis of MCC, its site within the radiation field (radio-dermatitis), the description of similar cases in the literature concerning the onset of MCC in irradiated areas, and the known carcinogenic effects of ionizing radiation all militate strongly in favour of the radiation-induced nature of MCC.